Design Modeling and CFD Simulation of Parallel Plate–Fin Heat Sink Under Natural Convection - Nguyen, Tue Duy; Vo, An Van; Bui, Tam Thanh (UI Scholars Hub, 2024)
The lifetime of electronic devices strongly depends on the junction temperature. Heat sinks are a good choice for dissipating heat because of their enhanced heat transfer areas. Plate–fin heat sinks are commonly used for electronic components because of their simple construction. Recently, computational fluid dynamics (CFD) software, such as Ansys Fluent and OpenFOAM, has been widely used and has provided effective results. Autodesk CFD is a powerful simulation tool; however, its use in heat sink research remains relatively uncommon. In this study, two plate–fin heat sinks with heights of 30 and 50 mm were first designed using heat transfer equations and then compared with Autodesk CFD simulations under natural convection conditions. Temperature inputs of 60 °C, 70 °C, and 80 °C were assigned to determine the temperature distribution along the fins, heat dissipation, fin efficiency, and fin effectiveness for both types of heat sinks. The results of the heat transfer calculations and Autodesk CFD simulations are consistent, with negligible differences. These findings indicate that Autodesk CFD can produce reliable results for heat sink design. In addition, efficiency decreases with the increase in fin height, although the effectiveness and heat dissipation of the tall (50 mm) heat sink are higher than those of the short (30 mm) heat sink. Although the 50-mm-high fin heat sink has a heat transfer area approximately 63% larger than that of the 30-mm-high fin heat sink, its heat dissipation is only approximately 40% larger than that of the 30-mm-high fin heat sink. This finding indicates that the addition of more material alone may not proportionally increase heat transfer and could lead to wasted material. Therefore, when designing heat sinks, the height of the fins should be carefully considered and optimized to enhance efficiency and conserve materials.